Zebrafish as a robust preclinical platform for screening plant-derived drugs with anticonvulsant properties—a review - Knap, Bartosz; Nieoczym, Dorota; Kundap, Uday; Kusio-Targonska, Kamila; Kukula-Koch, Wirginia; Turski, Waldemar A.; Gawel, Kinga (Frontiers in Molecular Neuroscience, 2023)
Traditionally, selected plant sources have been explored for medicines to treat convulsions. This continues today, especially in countries with low-income rates and poor medical systems.However, in the low-income countries, plant extracts and isolated drugs are in high demand due to their good safety profiles. Preclinical studies on animal models of seizures/epilepsy have revealed the anticonvulsant and/or antiepileptogenic properties of, at least some, herb preparations or plant metabolites. Still, there is a significant number of plants known in traditional medicine that exert anticonvulsant activity but have not been evaluated on animal models. Zebrafish is recognized as a suitable in vivo model of epilepsy research and is increasingly used as a screening platform. In this review, the results of selected preclinical studies are summarised to provide credible information for the future development of effective screening methods for plant-derived antiseizure/antiepileptic therapeutics using zebrafish models. We compared zebrafish vs. rodent data to show the translational value of the former in epilepsy research. We also surveyed caveats in methodology. Finally, we proposed a pipeline for screening new anticonvulsant plant-derived drugs in zebrafish ("from tank to bedside and back again").